SARS‐CoV‐2 spike protein enhances MAP4K3/GLK‐induced ACE2 stability in COVID‐19 - Chuang, Huai‐Chia; Hsueh, Chia‐Hsin; Hsu, Pu‐Ming; Huang, Rou‐Huei; Tsai, Ching‐Yi; Chung, Nai‐Hsiang; Chow, Yen‐Hung; Tan, Tse‐Hua (EMBO molecular medicine, 2022)
ACE2 on epithelial cells is the SARS‐CoV‐2 entry receptor. Single‐cell RNA‐sequencing data derived from two COVID‐19 cohorts revealed that MAP4K3/GLK‐positive epithelial cells were increased in patients. SARS‐CoV‐2‐induced GLK overexpression in epithelial cells was correlated with COVID‐19 severity and vesicle secretion. GLK overexpression induced the epithelial cell‐derived exosomes containing ACE2; the GLK‐induced exosomes transported ACE2 proteins to recipient cells, facilitating pseudovirus infection. Consistently, ACE2 proteins were increased in the serum exosomes from another COVID‐19 cohort. Remarkably, SARS‐CoV‐2 spike protein‐stimulated GLK, and GLK stabilized ACE2 in epithelial cells. Mechanistically, GLK phosphorylated ACE2 at two serine residues (Ser776, Ser783), leading to the dissociation of ACE2 from its E3 ligase UBR4. Reduction in UBR4‐induced Lys48‐linked ubiquitination at three lysine residues (Lys26, Lys112, Lys114) of ACE2 prevented its degradation. Furthermore, SARS‐CoV‐2 pseudovirus or live virus infection in humanized ACE2 mice induced GLK and ACE2 protein levels, and ACE2‐containing exosomes. Collectively, ACE2 stabilization by SARS‐CoV‐2‐induced MAP4K3/GLK may contribute to the pathogenesis of COVID‐19. Synopsis Induction of MAP4K3 (GLK) in epithelial cells from bronchoalveolar lavage fluid and nasopharynx of COVID‐19 patients is correlated with COVID‐19 severity and vesicle release. This study reports that GLK stabilizes ACE2 proteins, enhancing SARS‐CoV‐2 infection susceptibility of epithelial cells. GLK overexpression induces release of epithelial cell‐derived exosomes, which transport ACE2 to recipient cells in vitro and in vivo . Adoptive transfer of human ACE2‐containing exosomes allow wild‐type recipient mice to become susceptible to SARS‐CoV‐2 pseudovirus infection. SARS‐CoV‐2 spike protein increases GLK levels and subsequent ACE2 induction in epithelial cells and lung tissues of SARS‐CoV‐2‐infected mice. Mechanistically, GLK directly phosphorylates ACE2 at two specific serine residues (Ser776, Ser783), leading to reduction of UBR4‐mediated ubiquitination and degradation of ACE2 proteins. GLK‐mediated ACE2 phosphorylation is detected in serum exosomes or serum samples of COVID‐19 patients. Graphical Abstract Induction of MAP4K3 (GLK) in epithelial cells from bronchoalveolar lavage fluid and nasopharynx of COVID‐19 patients is correlated with COVID‐19 severity and vesicle release. This study reports that GLK stabilizes ACE2 proteins, enhancing SARS‐CoV‐2 infection susceptibility of epithelial cells.